Reconstruction of short-term storm surge-driven increases in shallow coastal lake salinity using ostracod shell chemistry - Lucy R. Roberts; Jonathan A. Holmes; David J. Horne; Melanie J. Leng; Carl D. Sayer; Rhys G. O. Timms; Katy Flowers; Simon P. M. Blockley; Andrea Kelly (Natural Hazards, 2022)

Riparian populations of minnesota reed canarygrass (Phalaris arundinacea) are most likely native, based on SNPs (DArTseqLD) - Andrzej K. Noyszewski; Neil O. Anderson; Alan G. Smith; Andrzej Kilian; Diana Dalbotten; Emi Ito; Anne Timm; Holly Pellerin; Barbora Kubátová; Tereza Kávová; Vojtěch Januš; Vladislav Čurn; et al. (Wetlands Ecology and Management, 2021)
The native vs. exotic status of reed canarygrass (RCG), a major invasive species of Minnesota wetlands, is unknown. The aim of this study was to investigate this native vs. exotic status to enhance its management. Genetic comparison of wild RCG populations from six Minnesota and six Czech Republic rivers was performed. A total of 2521 polymorphic SNP markers (single nucleotide polymorphisms) were used to evaluate 478 RCG samples across all collections. In the PCoA, all (n = 256) tested extant wild, riparian RCG genotypes from six Minnesota Rivers and six Czech Republic Rivers were genetically distinct, although some SNPs were common in both populations since they are the same species. DAPC analysis also resulted in the formation of two primary clusters separating the Minnesota Rivers and Czech Republic Rivers riparian samples, with little overlap; STRUCTURE analysis also supported this clustering with k = 4 groups as it separated the Czech Republic Rivers populations into three groups, along with Minnesota Rivers. The uniformity of PCoA, DAPC, STRUCTURE, and Evanno results indicates the distinct separation of Minnesota Rivers and Czech Republic Rivers populations. Portions of the genome (specific SNPs) are preserved or in common across continents, as indicated by STRUCTURE similarities. Nonetheless, overall significant SNP differences between the continents indicate that the Minnesota riparian populations are distinct enough from the European (Czech) collections to be delineated as native N. American RCG. PCoA of all the Minnesota RCG collections clustered Minnesota Rivers, Herbarium, Extant Herbarium, Research Field and Native Field collections together. STRUCTURE analysis (k = 2; Evanno) divided these Minnesota collections from the Commercial Field and Cultivars collections. There are two genetically distinct groups of RCG in Minnesota and since the Minnesota Rivers, the Research Field, the Native Field and pre-1930 herbaria collections clustered together, they are most likely native N. American types. Analysis of molecular variance (AMOVA) indicated that the genetic variation was more significant within, rather than among, the RCG populations. Native, historic herbaria types cluster together with all wild RCG river populations in Minnesota, all of which were distinct from those in Central Europe, suggesting native RCG type persistence in N. America. Also, cultivated forage types of RCG are distinct from wild RCG Minnesota river populations. The SNP genetic data shows that riparian Minnesota RCG populations are native. These data will facilitate future management strategies to control RCG as a native, but invasive, species.

Flow cytometric analysis of lymphocyte subpopulations in bronchoalveolar lavage fluid after repeated ozone exposure - O. Holz; M. Böttcher; P. Timm; S. Koschyk; G. Abel; G. Gercken; H. Magnussen; R. A. Jörres (International Archives of Occupational and Environmental Health, 2001)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

s 60th annual meeting The Potato Association of America - R. Kunkel; N. M. Holstad; R. E. Thornton; J. C. Bishop; Herman Timm; V. C. Shekhar; W. M. Iritani; Thornton Robert; Gary Hyde; Malamud Oscar; Robert B. O’Keefe; Mccown Brent; et al. (American Journal of Potato Research, 1976)